Assessing the Impact of Tourist Incivility, Job Satisfaction and Job Satisfaction on Trekking Guides Vocational Commitment - Dulal, Mandip; Karki, Bikram (KIC International Journal of Social Science and Management, 2024)
In the dynamic hospitality industry, employees engage deeply with customers, often becoming the organization's face. This study investigates the influence of tourist incivility, job stress, and job satisfaction on the vocational commitment of trekking guides. Using a quantitative research approach with a descriptive and correlational design, the study explores these relationships through hypotheses derived from existing literature. Out of 384 Participants, primarily male (96.67%) and aged 26-35 years (57%), were recruited via convenience sampling from diverse geographical locations. The results reveal significant positive correlations between job satisfaction factors (JSF) and vocational commitment (VC) (r = .267, p